Impact of dynamics of the frame on the performance of the positioning servosystem. (3rd October 2016) - Miková, Ľubica; Gmiterko, Alexander; Frankovský, Peter; Hroncová, Darina
The article deals with the issue of the impact of parasitic dynamics caused by vibroisolation on the performance of the positioning system in low- and high-frequency regions. Based on the simplified structure of the positioning system and passive vibroisolation system with one degree of freedom, a new structure of the positioning system is created taking into account the impact of vibroisolation system. By utilizing this structure of the positioning system based on the simulation, the impact of the ratio of the weight of the actuator to the frame weight and the damping factor on the performance of the positing system in low- and high-frequency regions is demonstrated.